Role of agromet advisories in climate risk management - Rao, V.U.M.; Rao, B. Bapuji (Annals of Agricultural Research, 2014)
Advance information on possible weather conditions that are likely to occur in the next 48 to 72 hours is very useful in farm operations as Indian agriculture is highly vulnerable to weather. Agrometeorological advisories, if properly designed and disseminated in time, enhances productivity on one hand and reduces the cost of production on the other. Advances made in the communication technology need to explored to the utmost to achieve the production potential of agri-horticultural systems. A brief account on the genesis, agencies involved, methodology adopted at present in the development-dissemination of agromet advisories and their utility in the context of present day agriculture is presented here. Tools helpful in the preparation of advisories with few examples and a case study on the dissemination of agromet advisories at the micro level are discussed.